The Cellular Apoptosis Susceptibility Protein (CAS) Promotes Tumor Necrosis Factor-related Apoptosis-inducing Ligand (TRAIL)-induced Apoptosis and Cell Proliferation - Monian, Prashant (J Biol Chem, 2016)
A signature event during the cell intrinsic apoptotic pathway is mitochondrial outer membrane permeabilization, leading to formation of the apoptosome, a caspase activation complex. The cellular apoptosis susceptibility protein (CAS) can facilitate apoptosome assembly by stimulating nucleotide exchange on Apaf-1 following binding of cytochrome c. We report here that CAS expression itself is up-regulated during tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-induced apoptosis, and knockdown of CAS renders cells resistant to TRAIL. We find that TRAIL induces up-regulation of CAS in a posttranscriptional, caspase-8-dependent manner through degradation of cIAP1, an E3 ligase that targets CAS for ubiquitin-dependent proteasomal degradation. We identified a novel signaling pathway whereby caspase-8 engages a feedforward cascade that leads to CAS up-regulation and amplifies the apoptotic signal. Furthermore, in silico analysis revealed that expression of CAS is up-regulated at both the mRNA and DNA levels in human breast tumors, consistent with its role in promoting cell proliferation. Overexpression of various oncogenes led to CAS up-regulation in non-transformed cells. Intriguingly, oncogene-induced CAS up-regulation also resulted in greater susceptibility to TRAIL-induced cell death, consistent with its proapoptotic function. These findings suggest that CAS plays contrasting roles in proliferation and apoptosis and that overexpression of CAS in tumors could serve as a potential biomarker to guide therapeutic choices.